Edukasi komprehensif penyakit mata kering di Puskesmas Dempo Palembang - Purwanita, Petty; Amin, Ramzi; Tribowo, Anang; Cicilia, Monica Putri (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Educational Outreach on Dry eye disease at Puskesmas Dempo Palembang. Dry eye disease is one of the most common eye health concerns worldwide, including in our community. With modern lifestyle changes, such as increased use of digital devices and exposure to less favorable environmental conditions, the prevalence of dry eye is rising. This condition not only causes daily discomfort but can also lead to serious vision problems if not properly addressed. The Community Ophthalmology Team from the Department of Ophthalmology, Faculty of Medicine, Sriwijaya University, conducted an outreach program to enhance participants' understanding of dry eye disease, covering its causes, symptoms, prevention, and treatment. Through effective education, we can help the community recognize early signs of the disease, adopt habits that support eye health, and seek appropriate treatment early on. A total of 32 participants, who were patients of Puskesmas Dempo, actively participated in the outreach program. The participants showed great enthusiasm during the Q&A session, and observations revealed an increase in their knowledge about dry eye disease. This outreach program successfully enhanced the community's awareness of dry eye disease and the steps to prevent it.